Anti-oxidation and anti-corrosion coating for aluminum electrolysis carbon anode and preparation method of anti-oxidation and anti-corrosion coating

By using aluminum electrolytic carbon anode anti-oxidation and corrosion protection coating with high alumina components, combined with materials such as sodium water glass and fluorinated graphite, the problems of poor oxidation resistance and short shelf life of existing coatings are solved, and the problem of existing coatings is achieved. It can effectively prevent oxidation and corrosion, and reduce the production cost of electrolytic aluminum.

CN119286293AActive Publication Date: 2025-01-10ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411582124.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-10
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing aluminum electrolytic carbon anode coating has poor oxidation resistance, short shelf life, and the content of boric acid and other compounds will affect the electrolytic efficiency of electrolytic aluminum, neglecting the corrosion of fluoride in the production environment on the coating, resulting in poor performance.

Method used

It adopts an aluminum electrolytic carbon anode anti-oxidation and anti-corrosion coating with a high alumina component. It uses white corundum powder, red corundum powder, microcrystalline corundum powder and other materials, combined with sodium water glass and potassium water glass as the binder. Add anticorrosion additives such as graphite fluorinated to form a fine insulation layer to prevent oxidation and corrosion.

Benefits of technology

It effectively reduces the high-temperature oxidation loss of the carbon anode, extends the shelf life of the paint, improves the anti-oxidation effect, avoids the corrosion of the paint by the electrolyte, and reduces the production cost of electrolytic aluminum. The weight loss rate is only 0.8%, which does not affect the electrolytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123392930000091
    Figure BDA0005123392930000091
  • Figure BDA0005123392930000101
    Figure BDA0005123392930000101
  • Figure BDA0005123392930000111
    Figure BDA0005123392930000111
Patent Text Reader

Abstract

The invention discloses an anti-oxidation and anti-corrosion coating for an aluminum electrolysis carbon anode and a preparation method of the anti-oxidation and anti-corrosion coating, the coating comprises the following components in percentage by mass: 30%-40% of a main component, 15%-25% of a secondary component, 10%-15% of a binder, 15%-25% of an anti-corrosion additive and the balance of water, and the main component comprises white corundum powder, red corundum powder and microcrystalline corundum powder; the secondary component comprises a secondary component 1 and a secondary component 2, and the secondary component 1 comprises phlogopite, biotite and soda mica; the secondary component 2 comprises potassium feldspar, albite and anorthite; the binder is sodium water glass and potash water glass. The anti-oxidation and anti-corrosion coating for the aluminum electrolysis carbon anode is simple and convenient to prepare, the carbon anode in work can be well protected after being coated with the anti-oxidation and anti-corrosion coating, the weight loss ratio of samples of all embodiments is calculated to be only about 0.8%, and the problems of anode oxidation and coating corrosion are effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses an anti-oxidation and anti-corrosion coating for an aluminum electrolysis carbon anode and a preparation method thereof, and belongs to the field of aluminum electrolysis, in particular to the field of carbon anode protection. Technical Background

[0002] Aluminum and aluminum alloys are widely used in aerospace, construction, transportation, electronic communications, defense and military industries due to their low density, high specific strength, corrosion resistance, easy processing, good thermal conductivity and electrical conductivity, and recyclability. Modern electrolytic aluminum industry production adopts cryolite-alumina molten salt electrolysis, with carbonite as the anode and aluminum liquid as the cathode. After a strong direct current is passed through, an electrochemical reaction is carried out at the two electrodes in the electrolytic cell at 800℃~960℃. The chemical reaction is mainly carried out through this equation: 2Al2O3+3C==4Al+3CO2↑,

[0003] ˉ-ˉ

[0004] Anode: 2O 2 +C-4e=CO2↑, cathode:Al 3+ +3e=Al. The carbon anode is the key to aluminum electrolysis. At present, the consumption of carbon anode for producing one ton of metal aluminum is 470 kg, which is 30% more than the theoretical carbon anode consumption. This is because after the carbon anode is replaced in the electrolytic cell, the cell temperature rises and the temperature of the conductive effect rises. The carbon anode is in contact with the air and the gas produced by electrolysis such as carbon dioxide, carbon monoxide, hydrogen fluoride, etc. at a high temperature above 900°C, resulting in high-temperature oxidation, chemical consumption, and the carbon particles fall off to form carbon slag. In order to reduce the high-temperature oxidation consumption of the carbon anode and reduce the production cost of electrolytic aluminum, the current economical and effective method is to apply a layer of protective coating on the surface of the carbon anode to reduce the high-temperature oxidation loss of the carbon anode caused by air, thereby extending the service life of the carbon anode.

[0005] At present, most aluminum electrolysis plants use the coating method to ensure that the carbon anode is isolated from the air to avoid additional losses caused by chemical consumption between the carbon anode and the air at high temperatures. However, they all have their defects. For example, the coating invented by the patent published in CN201510442632 has too low alumina content, resulting in poor oxidation resistance of the coating and a short shelf life of the coating. The coating invented by the patent published in CN202110738852 contains compounds such as boric acid and boric acid, which will have a certain impact on the electrolyte of electrolytic aluminum and reduce the electrolysis efficiency. In addition, these coatings also ignore the corrosion of fluorides produced in the production environment to the coating, which causes the coating performance to deteriorate and affects the anti-oxidation effect.

[0006] Therefore, in order to prevent the high-temperature surface oxidation corrosion of the carbon anode, the present invention provides a coating that can form a fine insulating layer on the surface of the carbon anode to prevent the oxidation of air and the carbon anode to cause additional consumption, and in the electrolytic aluminum environment, it can effectively prevent the electrolyte from corroding the coating. The weight loss rate is only 0.8% calculated by experiments, which greatly reduces the cost of electrolytic aluminum. Summary of the invention

[0007] In view of the above problems, the purpose of the present invention is to provide an anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode and a preparation method thereof. The preparation of the anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode provided by the invention is simple and convenient. After being coated on the carbon anode, the coating has a low sintering temperature and a short curing time. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode of the present invention can provide good protection for the carbon anode in operation. The weight loss rate of the samples in each embodiment is only about 0.8%, which effectively reduces the problems of anode oxidation and coating corrosion.

[0008] The technical solution adopted by the present invention is as follows:

[0009] An aluminum electrolytic carbon anode anti-oxidation and anti-corrosion coating comprises the following components by mass percentage: 30% to 40% of a main component, 15% to 25% of a secondary component, 10% to 15% of a binder, 15% to 25% of an anti-corrosion additive, and the balance being water;

[0010] The main components include white corundum powder, red corundum powder and microcrystalline corundum powder;

[0011] The subcomponents include subcomponent 1 and subcomponent 2, subcomponent 1 includes phlogopite, biotite and sodium mica; subcomponent 2 includes potassium feldspar, sodium feldspar and calcium feldspar;

[0012] The binder is sodium water glass and potassium water glass;

[0013] The anti-corrosion additives include one or more of anti-corrosion additives 1, anti-corrosion additives 2 and anti-corrosion additives 3; anti-corrosion additive 1 includes one or more of fluorinated graphite, fluorinated carbon black, fluorinated carbon fiber, fluorinated graphite microsheets, and fluorinated graphene; anti-corrosion additive 2 includes one or more of methyl trifluoroacrylate, perfluoromethyl acrylate, ethyl trifluoroacrylate, and perfluoroethyl acrylate; anti-corrosion additive 3 includes one or more of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDV, and polyvinyl fluoride PVF.

[0014] Furthermore, the main component is composed of raw materials in the following mass ratio: 40% to 60% of white corundum powder, 30% to 40% of red corundum powder, and 10% to 22% of microcrystalline corundum powder.

[0015] Furthermore, the white corundum powder has an Al2O3 content of 95% to 99%, a Na2O content of 0.01% to 0.05%, and a particle size between 180 mesh and 300 mesh; the red corundum powder has an Al2O3 content of 90% to 95%, a Cr2O3 content of 1% to 3%, and a particle size between 100 mesh and 200 mesh; the microcrystalline corundum powder has an Al2O3 content of 91% to 94%, a TiO2 content of 0.5% to 2%, and a particle size between 200 mesh and 300 mesh.

[0016] Furthermore, the subcomponent is composed of raw materials in the following mass ratios: 7% to 19% phlogopite, 12% to 20% biotite, 14% to 25% sodium mica, 14% to 28% potassium feldspar, 8% to 26% sodium feldspar, and 13% to 30% calcium feldspar.

[0017] Furthermore, the binder is composed of the following raw materials in the following mass ratio: 67% to 80% of sodium water glass and 20% to 33% of potassium water glass.

[0018] Furthermore, the Na2O content of sodium water glass is 4% to 10%, the SiO2 content is 15% to 44%, and the balance is deionized water; the K2O content of potassium water glass is 3% to 10%, the SiO2 content is 15% to 45%, and the balance is deionized water.

[0019] Furthermore, the anti-corrosion additive 1 is composed of the following raw materials in mass ratio: 0% to 20% of fluorinated graphite, 0% to 25% of fluorinated carbon black, 0% to 30% of fluorinated carbon fiber, 0% to 30% of fluorinated graphite microflakes, and 0% to 25% of fluorinated graphene; the anti-corrosion additive 2 is composed of the following raw materials in mass ratio: 0% to 40% of methyl trifluoroacrylate, 0% to 40% of perfluoromethyl acrylate, 0% to 30% of ethyl trifluoroacrylate, and 0% to 30% of perfluoroethyl acrylate; the anti-corrosion additive 3 is composed of the following raw materials in mass ratio: 0% to 60% of polytetrafluoroethylene PTFE, 0% to 60% of polyvinylidene fluoride PVDV, and 0% to 60% of polyvinyl fluoride PVF.

[0020] Most preferably, the carbon anode anti-oxidation and anti-corrosion coating comprises the following components by mass percentage: 30.7% to 38% of the main component, 17% to 22% of the secondary component, 10.9% to 14% of the binder, 17% to 25% of the anti-corrosion additive, and the balance is water. The main component is composed of the following raw materials in the following mass ratio: 42% to 56% of white corundum powder, 32% to 38% of red corundum powder, and 12% to 20% of microcrystalline corundum powder. The secondary component is composed of the following raw materials in the following mass ratio: 11% to 18% of phlogopite, 12% to 18% of biotite, 16% to 25% of sodium mica, 21% to 28% of potassium feldspar, 21% to 26% of sodium feldspar, and 13% to 18% of calcium feldspar. The binder is composed of the following raw materials in the following mass ratio: 72% to 78% of sodium water glass and 22% to 27% of potassium water glass. The anti-corrosion additive with a content of 17% to 25% is composed of raw materials with the following mass ratio: anti-corrosion additive 1 with a content of 8% to 13%, anti-corrosion additive 2 with a content of 4% to 13%, and anti-corrosion additive 3 with a content of 5% to 10%.

[0021] The method for preparing an anti-oxidation and anti-corrosion coating for an aluminum electrolytic carbon anode comprises the following specific steps: first weighing the raw materials of each component, mixing the main component with the secondary component to obtain a mixture A, mixing a binder and an anti-corrosion additive to obtain a mixture B, and then pouring the mixture A, the mixture B and water into a stirring tank in sequence, and stirring them thoroughly to obtain the anti-oxidation and anti-corrosion coating.

[0022] Furthermore, the preparation of the mixture A is specifically as follows: white corundum powder, red corundum powder, microcrystalline corundum powder, phlogopite, biotite, sodium mica, potassium feldspar, sodium feldspar, and calcium feldspar are sequentially put into a powder machine, and the mixture A is obtained after the machine is started for 2 to 6 hours;

[0023] The preparation of mixture B is specifically as follows: sodium water glass, potassium water glass, antiseptic additives and an appropriate amount of water are put into a magnetic stirrer in sequence, the stirring temperature is 20 to 60° C., preferably 30 to 80° C., the stirring speed is 200 to 600 rpm, and the stirring is performed for 1 to 5 hours, preferably 3 to 6 hours, to obtain mixture B.

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] 1) The prepared coating contains a relatively high content of aluminum oxide components, which can effectively wrap the carbon anode, block the erosion of oxygen, greatly reduce the oxidation rate, and have a good anti-oxidation effect; the prepared coating contains a moderate content of silicon oxide components, the coating has good extensibility, can effectively prevent the coating from settling, and greatly extend the shelf life of the coating; the prepared coating does not contain sulfur, phosphorus and other substances, will not produce substances harmful to electrolysis, and will not affect the efficiency of electrolytic aluminum; the prepared coating contains little metal except aluminum, and is very effective in preventing metal corrosion; the prepared coating contains fluorinated materials, which are resistant to corrosive chemicals such as strong acids, strong alkalis and strong oxidants, and are tightly arranged on the surface of the coating, which can effectively prevent the fluoride generated by the electrolytic environment from corroding the coating material.

[0026] 2) In addition, the anti-oxidation and anti-corrosion coating prepared by the present invention also has great advantages in practical application: the preparation of the coating of the present invention does not use expensive raw materials such as nanomaterials, and the cost of the prepared coating is only 5-7 yuan per kilogram; after the coating is coated on the surface of the carbon anode, the weight loss rate of the carbon anode of each embodiment is calculated to be only 0.8%; the raw materials required for the coating prepared by the present invention are widely available, the preparation is simple, and it is easy to promote. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0028] The white corundum powder, red corundum powder and microcrystalline corundum powder used in the embodiments of the present invention were purchased from Zhengzhou Rongsheng Kiln Engineering Technology Co., Ltd. Phlogopite, biotite, sodium mica, potassium feldspar, sodium feldspar and calcium feldspar were purchased from Anhui Ge Rui New Materials Technology Co., Ltd. The anticorrosive additives were purchased from Fuzhou Taipuda New Materials Co., Ltd. The carbon anode material was a blast furnace carbon block of the carbon block type.

[0029] Example 1

[0030] The invention discloses an anti-oxidation and anti-corrosion coating for an aluminum electrolytic carbon anode, which is composed of a main component, a secondary component, a binder, and anti-corrosion additive materials, calculated by weight percentage: the main component content is 30.7%, of which white corundum powder is 13.8%, red corundum powder is 11.1%, and microcrystalline corundum powder is 5.8%; the secondary component 1 content is 8.3%, of which phlogopite is 2.3%, biotite is 3.0%, and sodium mica is 3.0%; the secondary component 2 content is 10.5%, of which potassium feldspar is 4.5%, sodium feldspar is 4.1%, and calcium feldspar is 1.9%; the binder content is 11.5%, of which sodium water glass is 8.7%, and potassium water glass is 2.8%; the anti-corrosion additive 1 content is 22.9%, of which fluorinated carbon black is 4.8%, fluorinated carbon fiber is 5.7%, fluorinated graphite microsheets are 6.8%, and fluorinated graphene is 5.6%; the content of anti-corrosion additives 2 and 3 is both 0; the balance is water, and the total addition amount is 100%.

[0031] Sodium water glass is composed of the following raw materials by weight percentage: Na2O 10%, SiO2 40%, and the balance is water. Potassium water glass is composed of the following raw materials by weight percentage: K2O 10%, SiO2 45%, and the balance is water.

[0032] First, corundum powder, phlogopite, biotite, sodium mica, potassium feldspar, sodium feldspar and calcium feldspar are added to the powder machine in sequence, the powder machine is started, and after pulverizing for 4 hours, a mixture A with a powder mesh number of 220 is collected. Then, sodium water glass, potassium water glass, anticorrosive additives and an appropriate amount of water are added to the magnetic stirrer, the stirring temperature is 30°C, the stirring speed is 400rpm, and the stirring is carried out for 4 hours to obtain a mixture B; then the mixture A, the mixture B and the water are poured into the stirring kettle in sequence, the stirring temperature is 50°C, the stirring speed is 500rpm, the stirring time is 5h, and the anti-oxidation and anti-corrosion coating is obtained after sufficient stirring.

[0033] The anti-oxidation and anti-corrosion coating of Example 1 was applied to the surface of the carbon anode and sintered at 410°C in a hydrogen atmosphere for 2 hours. It was found that the coating was tightly wrapped on the surface of the carbon anode without falling off. The coating thickness on the surface of the carbon anode was 13 μm.

[0034] The coated carbon anode of Example 1 was placed in a tube furnace, the temperature was set to 910°C, CO2 gas was introduced at a constant temperature for 72 hours, and the gas introduction rate was 1 mL / min, to simulate the oxidation of the carbon anode during electrolysis. After the test was completed, the calculated weight loss rate was only 0.80%. The coating was tested again after 3 months of storage, and the weight loss rate was 0.81%. The coating was tested again after 6 months of storage, and the weight loss rate was 0.83%.

[0035] Weight loss rate = (M 测试前 -M 测试后 ) / M 测试前 ×100%.

[0036] In addition, the electrode efficiency test of the carbon anode after coating in Example 1 was carried out, and the test conditions were as follows: cryolite-alumina was added to the graphite electrolytic cell, heated to 900°C to melt the alumina (cryolith was used to lower the melting point of alumina and did not participate in the electrolysis process), the lower end of the carbon anode coated with the coating was inserted into the molten electrolyte, the upper end of the carbon anode was connected to the positive electrode of the power supply through a wire, and the negative electrode of the power supply was directly connected to the top of the graphite electrolytic cell through a wire, and the electrolysis reaction was carried out under power, and the electrolysis current was 60kA. The aluminum precipitated by electrolysis was deposited in the lower layer of the electrolyte, and the bottom aluminum product was output and then cooled and weighed.

[0037] An aluminum plant applied the coating on the carbon anode and tested it in a small side-insertion rod self-baking anode aluminum electrolysis below 60kA. The current efficiency of the electrolytic aluminum was 87.2%, with no obvious change.

[0038] Current efficiency = mass of aluminum actually deposited by electrolysis / mass of aluminum theoretically deposited by electrolysis × 100% (electrolysis time is 24 hours).

[0039] Example 2

[0040] The invention discloses an anti-oxidation and anti-corrosion coating for an aluminum electrolytic carbon anode, which is composed of a main component, a secondary component, a binder and anti-corrosion additive materials, calculated by weight percentage: the main component content is 31.1%, of which white corundum powder is 17.4%, red corundum powder is 10.0% and microcrystalline corundum powder is 3.7%; the secondary component 1 content is 8.6%, of which phlogopite is 2.2%, biotite is 3.2% and sodium mica is 3.2%; the secondary component 2 content is 11.5%, of which potassium feldspar is 4.8%, sodium feldspar is 4.4% and calcium feldspar is 2.2%; the binder content is 10.9%, of which sodium water glass is 7.7% and potassium water glass is 3.2%; the anti-corrosion additive 2 content is 18.1%, of which methyl trifluoroacrylate is 4.6%, methyl perfluoroacrylate is 5.4%, ethyl trifluoroacrylate is 4.5% and ethyl perfluoroacrylate is 3.6%; the content of anti-corrosion additives 1 and 3 is both 0; the balance is water, and the total addition amount is 100%.

[0041] Sodium water glass is composed of the following raw materials by weight percentage: Na2O4%, SiO244%, and the balance is water. Potassium water glass is composed of the following raw materials by weight percentage: K2O5%, SiO239%, and the balance is water.

[0042] Example 2 The preparation method of the anti-oxidation and anti-corrosion coating is repeated in Example 1.

[0043] The anti-oxidation and anti-corrosion coating of Example 2 was applied to the surface of the carbon anode and sintered at 410°C in a hydrogen atmosphere for 2 hours. It was found that the coating was tightly wrapped on the surface of the carbon anode without falling off. The coating thickness on the surface of the carbon anode was 13 μm.

[0044] Example 2 The coated carbon anode was subjected to high temperature oxidation test and current efficiency test, and the test conditions were repeated in Example 1. After the high temperature oxidation test was completed, the calculated weight loss rate was only 0.79%. The coating was tested again after 3 months of storage, and the weight loss rate was 0.81%. The coating was tested again after 6 months of storage, and the weight loss rate was 0.82%. An aluminum plant applied the coating and tested it in a small side-inserted self-baking anode aluminum electrolysis below 60kA. The current efficiency of electrolytic aluminum was 88.2%, with no significant change.

[0045] Example 3

[0046] The invention discloses an anti-oxidation and anti-corrosion coating for an aluminum electrolytic carbon anode, which is composed of a main component, a secondary component, a binder, and anti-corrosion additive materials, calculated by weight percentage: the main component content is 32.1%, of which white corundum powder is 14.8%, red corundum powder is 10.9%, and microcrystalline corundum powder is 6.4%; the secondary component 1 content is 10.2%, of which phlogopite is 2.8%, biotite is 3.7%, and sodium mica is 3.7%; the secondary component 2 content is 13.0%, of which potassium feldspar is 56%, sodium feldspar is 5.1%, and calcium feldspar is 5.3%; the binder content is 12.9%, of which sodium water glass is 8.7%, and potassium water glass is 4.2%; the anti-corrosion additive 3 content is 17.0%, of which polytetrafluoroethylene (PTFE) is 4.4%, polyvinylidene fluoride (PVDV) is 7.3%, and polyvinyl fluoride (PVF) is 5.3%; the content of anti-corrosion additives 1 and 2 is both 0; the balance is water, and the total addition amount is 100%.

[0047] Sodium water glass is composed of the following raw materials by weight percentage: Na2O 8%, SiO2 30%, and the balance is water. Potassium water glass is composed of the following raw materials by weight percentage: K2O 5%, SiO2 40%, and the balance is water.

[0048] Example 3 The preparation method of the anti-oxidation and anti-corrosion coating is repeated in Example 1.

[0049] The anti-oxidation and anti-corrosion coating of Example 3 was applied to the surface of the carbon anode and sintered at 410°C in a hydrogen atmosphere for 2 hours. It was found that the coating was tightly wrapped on the surface of the carbon anode without falling off. The coating thickness on the surface of the carbon anode was 13 μm.

[0050] Example 3 The coated carbon anode was subjected to high temperature oxidation test and current efficiency test, and the test conditions were repeated in Example 1. After the high temperature oxidation test was completed, the calculated weight loss rate was only 0.80%. The coating was tested again after 3 months of storage, and the weight loss rate was 0.80%. The coating was tested again after 6 months of storage, and the weight loss rate was 0.81%. An aluminum plant applied the coating and tested it in a small side-inserted self-baking anode aluminum electrolysis below 60kA. The current efficiency of electrolytic aluminum was 87.7%, with no significant change.

[0051] See Table 1 for the components and contents of the coatings of more embodiments of the present invention.

[0052] Table 1 Content of each component of the coating in the embodiment

[0053]

[0054]

[0055] The components and contents of water glass in more embodiments of the present invention are shown in Table 2

[0056] Table 2 Content of each component of water glass

[0057]

[0058] The preparation steps of the anti-oxidation and anti-corrosion coatings of Examples 4-8 and Comparative Examples 4-8 refer to those of Example 1, and the conditions of coating the anti-oxidation and anti-corrosion coatings on the surface of the carbon anode for sintering, high-temperature calcination in a tubular furnace, and subsequent performance testing are all repeated in Example 1.

[0059] For more test data, see Table 3.

[0060] Table 3 Test results

[0061]

Claims

1. An anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode, characterized in that: The components include the following by mass percentage: main component 30%~40%, secondary component 15%~25%, binder 10%~15%, anticorrosive additive 15%~25%, and the balance is water; The main components include white corundum powder, red corundum powder and microcrystalline corundum powder; The subcomponents include subcomponent 1 and subcomponent 2, subcomponent 1 includes phlogopite, biotite and sodium mica; subcomponent 2 includes potassium feldspar, sodium feldspar and calcium feldspar; The binder is sodium water glass and potassium water glass; The anti-corrosion additives include one or more of anti-corrosion additives 1, anti-corrosion additives 2 and anti-corrosion additives 3; anti-corrosion additive 1 includes one or more of fluorinated graphite, fluorinated carbon black, fluorinated carbon fiber, fluorinated graphite microsheets, and fluorinated graphene; anti-corrosion additive 2 includes one or more of methyl trifluoroacrylate, perfluoromethyl acrylate, ethyl trifluoroacrylate, and perfluoroethyl acrylate; anti-corrosion additive 3 includes one or more of polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDV, and polyvinyl fluoride PVF.

2. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 1, characterized in that: The main component is composed of the following raw materials in the following mass ratio: 40% to 60% white corundum powder, 30% to 40% red corundum powder, and 10% to 22% microcrystalline corundum powder, preferably 42% to 56% white corundum powder, 32% to 38% red corundum powder, and 12% to 20% microcrystalline corundum powder.

3. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 2, characterized in that: The white corundum powder has an Al2O3 content of 95% to 99%, a Na2O content of 0.01% to 0.05%, and a particle size between 180 mesh and 300 mesh; the red corundum powder has an Al2O3 content of 90% to 95%, a Cr2O3 content of 1% to 3%, and a particle size between 100 mesh and 200 mesh; the microcrystalline corundum powder has an Al2O3 content of 91% to 94%, a TiO2 content of 0.5% to 2%, and a particle size between 200 mesh and 300 mesh.

4. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 1, characterized in that: The subcomponent is composed of the following raw materials in the following mass ratios: 7% to 19% phlogopite, 12% to 20% biotite, 14% to 25% sodium mica, 14% to 28% potassium feldspar, 8% to 26% sodium feldspar, and 13% to 30% calcium feldspar, preferably 11% to 18% phlogopite, 12% to 18% biotite, 16% to 25% sodium mica, 21% to 28% potassium feldspar, 21% to 26% sodium feldspar, and 13% to 18% calcium feldspar.

5. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 1, characterized in that: The binder is composed of the following raw materials in the following mass ratio: 67% to 80% of sodium water glass and 20% to 33% of potassium water glass, preferably 72% to 78% of sodium water glass and 22% to 28% of potassium water glass.

6. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 5, characterized in that: The Na2O content of sodium water glass is 4%~10%, the SiO2 content is 15%~44%, and the balance is deionized water; the K2O content of potassium water glass is 3%~10%, the SiO2 content is 15%~45%, and the balance is deionized water.

7. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 1, characterized in that: The anti-corrosion additive 1 is composed of the following raw materials in mass ratio: 0%-20% of fluorinated graphite, 0%-25% of fluorinated carbon black, 0%-30% of fluorinated carbon fiber, 0%-30% of fluorinated graphite microsheets, and 0%-25% of fluorinated graphene; the anti-corrosion additive 2 is composed of the following raw materials in mass ratio: 0%-40% of methyl trifluoroacrylate, 0%-40% of perfluoromethyl acrylate, 0%-30% of ethyl trifluoroacrylate, and 0%-30% of perfluoroethyl acrylate; the anti-corrosion additive 3 is composed of the following raw materials in mass ratio: 0%-60% of polytetrafluoroethylene (PTFE), 0%-60% of polyvinylidene fluoride (PVDV), and 0%-60% of polyvinyl fluoride (PVF).

8. The anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 1, characterized in that: The composition includes the following components by mass percentage: 30.7% to 38% of the main component, 17% to 22% of the secondary component, 10.9% to 14% of the binder, 17% to 25% of the anti-corrosion additive, and the balance is water; the 17% to 25% anti-corrosion additive is composed of the following raw materials in the following mass ratio: 8% to 13% of the anti-corrosion additive 1, 4% to 13% of the anti-corrosion additive 2, and 5% to 10% of the anti-corrosion additive 3.

9. The method for preparing an anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to any one of claims 1 to 8, characterized in that: The specific steps are as follows: first weigh the raw materials of each component, mix the main component with the secondary component to obtain mixture A, mix the binder and the anti-corrosion additive to obtain mixture B, and then pour mixture A, mixture B and water into a stirring tank in sequence, and stir thoroughly to obtain an anti-oxidation and anti-corrosion coating.

10. The method for preparing an anti-oxidation and anti-corrosion coating for aluminum electrolytic carbon anode according to claim 9, characterized in that: The preparation of mixture A is as follows: white corundum powder, red corundum powder, microcrystalline corundum powder, phlogopite, biotite, sodium mica, potassium feldspar, sodium feldspar, and calcium feldspar are sequentially put into a powder machine, and the mixture A is obtained after the machine is started for 2 to 6 hours; The preparation of mixture B is specifically as follows: sodium water glass, potassium water glass, antiseptic additives and an appropriate amount of water are put into a magnetic stirrer in sequence, the stirring temperature is 20-60°C, preferably 30-80°C, the stirring speed is 200-600 rpm, and the stirring is performed for 1-5 h, preferably 3-6 h, to obtain mixture B.

Citation Information

Patent Citations

  • Anti-oxidation coating for carbon anodes in aluminum electrolysis

    CN106702431A

  • Anti-oxidation coating for carbon anode and preparation method thereof

    CN115537878A

  • Prebaked anode anti-oxidation coating for electrolytic aluminum and preparation method of prebaked anode anti-oxidation coating

    CN115895302A

  • Antioxidant and anticorrosive coating for electrolytic aluminum carbon anode

    CN116606561A

  • Water-based inorganic high-temperature-resistant anticorrosive paint as well as preparation method and application thereof

    CN118620428A

Cited By

  • Mica-based anti-oxidation coating as well as preparation method and application thereof

    CN121227092A